Sea of Storms : A History of Hurricanes in the Greater Caribbean from Columbus to Katrina - Schwartz, Stuart B. (Book collections on Project MUSE., 2014)
The diverse cultures of the Caribbean have been shaped as much by hurricanes as they have by diplomacy, commerce, or the legacy of colonial rule. In this panoramic work of social history, the author examines how Caribbean societies have responded to the dangers of hurricanes, and how these destructive storms have influenced the region's history, from the rise of plantations, to slavery and its abolition, to migrations, racial conflict, and war. Taking readers from the voyages of Columbus to the devastation of Hurricane Katrina, this book looks at the ethical, political, and economic challenges hurricanes posed to the Caribbean's indigenous populations and the different European peoples who ventured to the New World to exploit its riches.